FLIP: Molecular switch between apoptosis and necroptosis. Issue 9 (26th April 2013) - Gong, JingJing; Kumar, Saikartik A.; Graham, Gilian; Kumar, Addanki P.
Abstract Cancerous growth is one of the most difficult diseases to target as there is no one clear cause, and targeting only one pathway does not generally produce quantifiable improvement. For a truly effective cancer therapy, multiple pathways must be targeted at the same time. One way to do this is to find a gene that is associated with several pathways; this approach expands the possibilities for disease targeting and enables multiple points of attack rather than one fixed point, which does not allow treatment to evolve over time as cancer does. Inducing programmed cell death (PCD) is a promising method to prevent or inhibit the progression of tumor cells. Intricate cross talk among various programmed cell death pathways including cell death by apoptosis, necroptosis or autophagy plays a critical role in the regulation of PCD. In addition, the complex and overlapping patterns of signaling and lack of understanding of such networks between these pathways generate hurdles for developing effective therapeutic approaches. This review article focuses on targeting FLIP (Fas‐associated death domain‐like interleukin‐1‐converting enzyme‐like inhibitory protein) signaling as a bridge between various PCD processes as an effective approach for cancer management. © 2013 Wiley Periodicals, Inc.